FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN PEMERIKSAAN KEHAMILAN DI WILAYAH KERJA PUSKESMAS TARUS TAHUN 2022 - Sisilia Sumiati Bili; Masrida Sinaga; Grace Martiani Maku (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Prenatal care is the supervision of pregnancy to determine the health of the mother, early enforce diseases that accompany pregnancy, early enforce pregnancy complications, and determine the risk of pregnancy. K4 coverage at the Tarus Health Center over the past three years has not reached the target of SPM sector set nationally (95%), namely in 2019 by 65.48%, in 2020 by 73.10%, and in 2021 by 70.48%. The purpose of this study was to determine the factors related to the utilization of pregnancy examination services in the Working Area of the Tarus Health Center in 2022. The type of research used is an analytical Survey study with a cross sectional study design on a sample of 58 mothers giving birth. This study was conducted in June-July 2022. Sampling technique in this study is by simple random sampling. Analysis of univariate and bivariate data with Chi Square test statistical test. The results showed that there is a relationship between the level of knowledge (p-value=0.000), maternal attitudes (p-value=0.000), family support (p-value=0.000) and family income (p-value=0.004) with the utilization of pregnancy screening services in the work area of Puskesmas Tarus. There was no relationship between the level of Education (p-value=0.229) with the use of pregnancy screening services in the Working Area of Puskesmas Tarus. It is expected that the Puskesmas seeks to improve the MCH program by conducting counseling related to the importance of pregnancy examination at least 6 times periodically that mothers can be motivated to take advantage of pregnancy examination services.